2014
DOI: 10.1111/rec.12102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biennial Fire and Clipping on Woody and Herbaceous Ground Layer Vegetation: Implications for Restoration and Management of Oak Barren Ecosystems

Abstract: Savannas and oak barrens are threatened in North America, due, in part, to removal of natural disturbance regimes. However, the periodic prescribed fires used in savanna and oak barren management sometimes accelerate the formation of a shrub layer, which can displace herbaceous species. This may be because periodic low severity fires act much like clipping, topkilling shrubs, yet allowing them to accumulate reserves in intervals without fire for more vigorous sprouting. To test this, we compared biennial dorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In several other studies, burning and cutting did not result in a different resprouting of individuals either (Pyke et al. ; Petersen & Drewa ), but our study is the first to demonstrate this for temperate European woody species.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In several other studies, burning and cutting did not result in a different resprouting of individuals either (Pyke et al. ; Petersen & Drewa ), but our study is the first to demonstrate this for temperate European woody species.…”
Section: Discussionsupporting
confidence: 64%
“…cutting or burning), causing the complete loss of the above‐ground biomass of woody species, induced similar resprouting rates, both in the field and the experimental study. This similarity indicates that none of the applied treatments damaged the collar meristems, which are vital for resprouting, although the treatments were severe enough to induce the resprouting process (see also Petersen & Drewa ). Despite the nutrient input to the soil from the burned above‐ground biomass (Blodgett et al.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Disturbance type (mowing versus burning) had a limited effect on resprouting dynamics of scrubby flatwoods shrub species. Similarly, many studies have found little difference in resprouting or woody cover after burning versus mowing or cutting or clipping (e.g., Hmielowski et al 2014;Peterson and Drewa 2014;Michielsen et al 2017). In contrast, some studies have found that burning results in higher mortality and lower post-disturbance growth than cutting (Peguero and Espelta 2011;Noble and Diggle 2014).…”
Section: Discussionmentioning
confidence: 99%